The biosynthesis of nicotinamide adenine dinucleotides in bacteria - Begley, Tadhg P; Kinsland, Cynthia; Mehl, Ryan A; Osterman, Andrei; Dorrestein, Pieter (Cofactor Biosynthesis: a Mechanistic Perspective, 2001)
The nicotinamide adenine dinucleotides (NAD, NADH, NADP, and NADPH) are essential cofactors in all living systems and function as hydride acceptors (NAD, NADP) and hydride donors (NADH, NADPH) in biochemical redox reactions. The six-step bacterial biosynthetic pathway begins with the oxidation of aspartate to iminosuccinic acid, which is then condensed with dihydroxyacetone phosphate to give quinolinic acid. Phosphoribosylation and decarboxylation of quinolinic acid gives nicotinic acid mononucleotide. Adenylation of this mononucleotide followed by amide formation completes the biosynthesis of NAD. An additional phosphorylation gives NADP. This review focuses on the mechanistic enzymology of this Dathwav in bacteria.